Gerakan Bengkel Ramah Difabel, Aman, Mandiri, Intelligent, dan Sehat di Masa Adaptasi Kebiasaan Baru Covid-19 - Dianna Ratnawati; Sigit Purnomo; Bernadetta Diansepti Maharani (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2022)
Community service activities for the RAMIS workshop movement (Disabled Friendly, Safe, Independent, Intelligent, and Healthy) include the following programs: (1) standardization of ergonomic disabled workshops, having SOPs for disabled motorcycle workshops, repairing workshop inventory, and obeying the principles of health protocols in work environment in the new normal life era; (2) motorcycle service training for workers; (3) launching of RAMIS workshop e-commerce and operation training. The objectives of this PKM include: (1) standardization of partner workshops into RAMIS workshops; (2) improving service skills and equipment maintenance skills for workers; (3) improve the quality of marketing and services through the RAMIS workshop e-commerce. The methods used to realize the program are pilot, training and mentoring. The PKM activity programs that have been implemented include: (1) completing the inventory of partner workshops and arranging workshop layouts; and (2) training and assistance for tricycle motorcycle service; (3) creation of an e-commerce web for partner workshops. The service training activity was attended by 20 participants. Based on the implementation of the PKM program, the results obtained are 100% complete workshop equipment, 100% skilled workers in maintaining workshop equipment, 85% skilled workers in carrying out tricycle motorcycle services, the RAMIS workshop e-commerce web can be accessed at www.bengkelramis.com. With the indicators of the achievement of the PKM program, it can be concluded that this service program activity has been carried out very well.